2010
DOI: 10.1063/1.3319717
|View full text |Cite
|
Sign up to set email alerts
|

Search for Br∗ production in the D+DBr reaction

Abstract: Deuterium bromide (DBr) is expanded from a pulsed jet into a vacuum and a synchronized pulsed laser causes photodissociation of some of the DBr molecules to produce primarily (approximately 85%) ground-state bromine atoms ((2)P(3/2)) and fast D atoms. The latter collide with the cold DBr molecules and react to produce molecular deuterium (D(2)) via two possible channels, the adiabatic channel D(2)+Br((2)P(3/2)) and the nonadiabatic channel D(2)+Br*((2)P(1/2)), which are asymptotically separated in energy by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…On the other hand, considering the magnitude of the ratio in Fig. 8, we come to the conclusion that the electronic nonadiabaticity only plays a minor role in the H + HBr and other variants which is in complete agreement with the experiment of Zare's [2]. In order to describe the BrH 2 system and verify the PES completely, further state-to-state dynamical calculations should be performed.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…On the other hand, considering the magnitude of the ratio in Fig. 8, we come to the conclusion that the electronic nonadiabaticity only plays a minor role in the H + HBr and other variants which is in complete agreement with the experiment of Zare's [2]. In order to describe the BrH 2 system and verify the PES completely, further state-to-state dynamical calculations should be performed.…”
Section: Resultssupporting
confidence: 69%
“…The BrH 2 system is currently under extensive study and has played an important role in the development and understanding of elementary chemical kinetics and reaction dynamics [1][2][3]. Interest in the reactivity of H + HBr reaction dates back 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct mechanisms are presented in their report: a direct reactive mechanism in which the trajectories stay near the collinear minimum energy path, and an indirect reactive mechanism in which the trajectories deviate significantly from the minimum energy path. Since the experiments mentioned above were unable to determine whether or not Br * is formed from the H + HBr reaction, they performed an experiment on the D + DBr (v = 0) reaction by the ion imaging method for the 1.43-2.11 eV collision energy range 12 to observe directly if Br * is formed. Instead of the H + HBr (v = 0) reaction, they chose the D + DBr (v = 0) reaction because this choice gave larger signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The second, an indirect reaction mechanism, has the H atom undergoing several collisions with HBr before the H 2 product is formed. A search for the nonadiabatic production of spin-orbit-excited Br in the D + DBr reaction showed that this channel contributes 1% or less for the conditions studied (54). The agreement between experiment and theory for the H + D 2 reaction is very good, although not yet perfect (34,35,(38)(39)(40).…”
Section: Wwwannualreviewsorg • the Hydrogen Games And Other Adventumentioning
confidence: 70%